Randall Collins and the Sociology of Emotions - Iagulli, Paolo (Italian Sociological Review, 2016)
The objective of this article is to illustrate the close relationship between the thought of Randall Collins - well-known in Italy for his manuals, less so for his more innovative works - and the sociology of emotions. The publication of his book Conflict Sociology (1975) was one of the most significant episodes in the emergence of this field of study towards the end of the 1970s. More importantly, though, Collins’ interaction ritual theory is inextricably linked to the emotions: his "ritual theory of emotions" is an integral part of IR theory and has become the theory of reference for what now constitutes an autonomous sociological approach to the emotions. Collins may be reproached for configuring the social actor as overly emotional, but obviously this is also a merit, if one considers for how long sociological theory was characterised by the primacy of normative and rational actors.